KONSEP KESEIMBANGAN DALAM EKONOMI SYARIAH: SOLUSI TERHADAP KESENJANGAN SOSIAL EKONOMI ERA KAPITALISME DIGITAL - Annisaturrahmi, Annisaturrahmi (JEB17 : Jurnal Ekonomi dan Bisnis, 2025)
Digital capitalism has significantly widened socio-economic disparities, with wealth and market power concentrated in the hands of a handful of global players. This system has failed to create distributive justice, thus making the problem of inequality increasingly acute and requiring paradigmatic solutions. The purpose of this research is to describe and analyze the concept of balance (tawazun) in Islamic economics: a solution to socio-economic disparities in the era of digital capitalism. This research uses a qualitative approach through library research methods. The data collection stage is carried out systematically through documentation methods. The results show that: 1). The deconstruction of digital capitalism is that digital capitalism has formed an oligopoly system in which a handful of giant platforms control digital data and infrastructure, creating structural inequalities through the attention economy and gig models that exploit labor. This inequity is not a systemic flaw, but rather an inherent feature of the logic of capital accumulation in the digital era. 2). The concept of tawazun in Islamic economics offers a holistic paradigm of balance that rejects inequality through three pillars: balance of ownership with the ZISWAF instrument (Zakat, Infaq, Sedekah, and Waqf), market balance with the prohibition of usury and monopoly, and balance of values with the principle of benefit as the ultimate goal. 3). The integration of the tawazun concept into the digital ecosystem is realized through a digital Islamic cooperative platform, profit-sharing-based fintech, and the use of digital ZISWAF for equitable access. At the regulatory level, the principles of data sovereignty and Islamic algorithm ethics are proposed, as well as Islamic digital economic literacy to empower communities.